Pre-Service Teachers’ Practices on Developing and Using Learning Devices During Practicum - Antoni, Rivi; Mustafa, Jamilah (Journal of Applied Linguistics, 2024)
Pre-service teachers’ practices of teaching and teacher training programs become an endless discussion among scholars and school communities in Indonesia. In EFL teacher training programs of university of Pasir Pengaraian, trainees are assigned to go for a teaching practicum in schools where they can experience the real classroom atmosphere. However, though trainees have prepared with English proficiency and pedagogic, they still find it difficult to practice. Thus, it is essential to explore further phenomena that might enlighten the programs in their endeavor to produce competent teachers especially on developing and using the learning devices. For this purpose, the researchers observed and interviewed twelve trainees from university Pasir Pengaraian who were on their practicum. This qualitative case study used rubrics from an observation instrument designed by the teacher’s association of Indonesia. The data were analysed on indicators of pedagogic competences. The results show that although pre-service teachers were prepared for the practicum, they find different practices in developing the learning devices and their uses by teacher training programme and school teachers. This finding has impacts on teacher preparation where the university needs to organize the programme to meet the needs of pre-service teachers and the current policies on school curriculum, and to collaborate closely with stakeholder to ensure both parties are involved. Keywords : Teacher training; Pedagogic; Learning devices;  Pre service teacher